2018
DOI: 10.1016/j.jaac.2018.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems and Onset of Tobacco Use Among 12- to 24-Year-Olds in the PATH Study

Abstract: Objective: To examine whether mental health problems predict incident use of 12 different tobacco products in a nationally representative sample of youth and young adults. Method: This study analyzed Wave (W) 1 and W2 data from 10,533 12-to 24-year-old W1 never tobacco users in the Population Assessment of Tobacco and Health (PATH) Study. Self-reported lifetime internalizing and externalizing symptoms were assessed at W1. Past 12-month use of cigarettes, electronic nicotine delivery systems (ENDS), traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 32 publications
(56 reference statements)
4
32
2
Order By: Relevance
“…In 2 longitudinal studies of college students and adolescents, elevated depressive symptoms were associated with increased risk of initiation of e-cigarette, combustible cigarette, and dual-product use 16,17 ; however, in neither of these studies did the authors adjust for externalizing problems. Interestingly, Green et al 13 found that internalizing problems were a predictor of initiation of combustible cigarette use even after controlling for externalizing problems, whereas we did not observe this association. This may reflect the more restricted age range or smaller sample size in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In 2 longitudinal studies of college students and adolescents, elevated depressive symptoms were associated with increased risk of initiation of e-cigarette, combustible cigarette, and dual-product use 16,17 ; however, in neither of these studies did the authors adjust for externalizing problems. Interestingly, Green et al 13 found that internalizing problems were a predictor of initiation of combustible cigarette use even after controlling for externalizing problems, whereas we did not observe this association. This may reflect the more restricted age range or smaller sample size in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results extend the findings of a recent article in which the authors examined a similar research question among 12- to 24-year-olds in the PATH sample. 13 First, Green et al 13 examined associations between mental health problems and initiation of electronic nicotine delivery system use, which included e-cigarettes, e-cigars, e-pipes, and e-hookahs, whereas we examined initiation of use of e-cigarettes only. On the basis of the current study, we can be more confident that mental health problems are associated with initiation of e-cigarette use specifically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An 18-item version of the Eysenck Personality Questionnaire, scored according to the established guide, was used to measure three dimensions of personality introversion-extraversion, neuroticism and psychoticism, and included as covariates in the multivariable regression model [23]. Tobacco use is known to be associated with all three dimensions of personality traits [24, 25]. Psychosocial and behavioral factors were considered as confounding regarding tobacco transistions from adolecence to adulthoood.…”
Section: Methodsmentioning
confidence: 99%